1994
DOI: 10.1093/carcin/15.7.1387
|View full text |Cite
|
Sign up to set email alerts
|

The selenium metabolite selenodiglutathione induces p53 and apoptosis: relevance to the chemopreventive effects of selenium?

Abstract: Selenodiglutathione (SDG), the initial metabolite of selenite, is shown to be a more powerful inhibitor of cell growth in vitro than selenite itself. This has been established both with mouse erythroleukaemia (MEL) cells and an ovarian cell line (A2780) which is known to contain wild-type p53. Other seleno-compounds, such as selenomethyl selenocysteine (SMS) and dimethyl selenoxide (DMS), which are potent chemopreventive agents and are known to be metabolized to methylated selenium derivatives directly rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(70 citation statements)
references
References 0 publications
5
61
1
3
Order By: Relevance
“…We also showed that overexpression of MnSOD prevented cell death from selenite treatment (26). In addition, studies from other laboratories have shown that selenium compounds modulated p53 (14,(27)(28)(29). Taken together, these results suggest that superoxide and p53 may be involved in apoptosis induced by selenite.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…We also showed that overexpression of MnSOD prevented cell death from selenite treatment (26). In addition, studies from other laboratories have shown that selenium compounds modulated p53 (14,(27)(28)(29). Taken together, these results suggest that superoxide and p53 may be involved in apoptosis induced by selenite.…”
Section: Introductionsupporting
confidence: 57%
“…Recent studies have shown that selenite treatment up-regulated p53 and induced p53 phosphorylation on Ser15 to induce caspasemediated apoptosis (27)(28)(29). However, the link between superoxide production and p53 regulation in selenite-induced apoptosis has not been elucidated.…”
Section: Selenite and Apoptosis Of Prostate Cancer Cellsmentioning
confidence: 99%
“…Our results concerning the relation between selenium and apoptosis in humans were contrary to results from several laboratory studies, suggesting that selenium increased anticancer apoptotic activity (34)(35)(36)(37)(38)(39)(40)(41)(42). There are several reasons that our results may differ from laboratory studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The possibility that selenium may increase anticancer apoptotic activity has been suggested by several carcinogenesis studies (34)(35)(36)(37)(38)(39)(40)(41)(42). It is unclear how selenium might induce apoptosis; however, several selenium metabolites, such as hydrogen selenide, methylselenol, and selenodiglutathione, are being researched (43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, whether an intact p53 system is necessary for any anticarcinogenic effects of selenium or vitamin E remains a contentious issue. While Lanfear et al (91) reported that selenium metabolite selenodiglutathione caused apoptosis in cells with wild-type and mutated p53 status (murine erythroleukemia and human ovarian carcinoma), Jiang et al (92) reported that selenite-induced apoptosis of LNCaP cells depends on intact p53 activity. The specific role of p53 in seleniuminduced PCa cell apoptosis, and perhaps in turn whether selenium acts preferentially via the intrinsic or extrinsic pathways, remains an active area of research.…”
Section: Selenium and Pca: Clinical Studiesmentioning
confidence: 99%